Evaluation of Antioxidant and Toxicological properties of Chicory leaves. - Ilaiyaraja, N (International Journal of Pharmaceutical & Biological Archive, 2010)
Antioxidant potential of various solvent extracts of Chicory (Cichorium intybus L) leaf was evaluated. Among the extracts, the aqueous extract showed maximum radical scavenging activity by DPPH method (87.45%) as well as total polyphenolic content (51.69 mg/g extract). The aqueous extract was further evaluated for its in vitro antioxidant potency toward reducing power, superoxide scavenging activity, metal chelating property and hydroxyl radical scavenging ability. Protection against radical induced protein oxidation (BSA) and DNA damage (by pBR322 plasmid DNA nicking assay and SCGE assay) were also evaluated. The results indicates that the aqueous extract of chicory posses a marked radical scavenging properties and offered significant protection against protein oxidation and DNA damage, which could be attributed to the presence of phenolic compounds. As for the safety is concerned; the extract did not cause any toxic symptoms at acute and sub chronic toxicity levels used in the study. Moreover, it also showed to be free of any cytotoxicity towards rat’s lymphocytes. Therefore, Chicory leaves can be considered as a source of natural antioxidants for pharmaceutical or dietary needs.